From Misconduct to Merit: Understanding How Backdated Publications Shape Academic Hierarchies - Bharti, Jaya; Kumar, Rakesh; Bhatnagar, Pallavi; Singh, Rashmi; Rathore, Dinesh (Science Insights, 2026)
This qualitative study investigates the growing phenomenon of backdated research publications and their influence on academic hierarchies within Indian higher education institutions. Conducted across four major university settings—Kanpur, Lucknow, Delhi, and Varanasi—the research engages a purposive sample of 200 faculty members, with 50 teachers from each location. Using a semi-structured interview schedule, the study explores personal experiences, perceptions, and observations related to unethical publication practices, institutional pressures, and career advancement mechanisms. The responses were analyzed through thematic analysis, generating ten major themes that capture the complexity of publication-related misconduct. These themes highlight issues such as systemic loopholes, pressure to publish, compromised peer review, the role of institutional politics, and the impact on both academic integrity and meritocracy. The findings emphasize an urgent need for transparent evaluation systems, ethical oversight, and awareness-driven reforms to safeguard the credibility of academic scholarship and promotion pathways.